1998
DOI: 10.1093/ndt/13.4.935
|View full text |Cite
|
Sign up to set email alerts
|

Antiglomerular basement membrane (GBM)-antibody-mediated disease with normal renal function

Abstract: Patients with anti-GBM disease with normal renal function are not uncommon, and often have a good prognosis. There is less renal damage, possibly because of lower levels of circulating anti-GBM antibodies and less glomerular complement deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 0 publications
1
38
1
7
Order By: Relevance
“…Pulmonary hemorrhage probably leads to earlier presentation and diagnosis before anuric renal failure ensues. That may partly due to an increased awareness of anti-GBM disease manifesting as hemoptysis or pulmonary hemosiderosis prior to, or with minimal renal involvement [10]. However, in our series, there was no difference about the initial serum creatinine between patients with lung hemorrhage prior to and after nephritis (p > 0.05), and early diagnosis was not achieved on the patients with pulmonary hemorrhage prior to renal involvement (70 vs. 43 days).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Pulmonary hemorrhage probably leads to earlier presentation and diagnosis before anuric renal failure ensues. That may partly due to an increased awareness of anti-GBM disease manifesting as hemoptysis or pulmonary hemosiderosis prior to, or with minimal renal involvement [10]. However, in our series, there was no difference about the initial serum creatinine between patients with lung hemorrhage prior to and after nephritis (p > 0.05), and early diagnosis was not achieved on the patients with pulmonary hemorrhage prior to renal involvement (70 vs. 43 days).…”
Section: Discussioncontrasting
confidence: 54%
“…Since intensive therapy with a combination of immunosuppression and plasma exchange was introduced, recent investigations documented a better survival [4, 5, 6, 7, 8, 9]. Furthermore, 15–36% of patients with anti-GBM disease were reported with normal renal function in one study [10]. Anti-GBM disease has been reported predominantly in the Caucasian population, and reports from Chinese were lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported 40-80% incidence of renal insufficiency in anti-GBM disease. [192021] In patients with rapidly progressive glomerulonephritis, Jennette et al . found raised serum creatinine at a presentation in most patients of anti-GBM nephritis (mean 9.7 ± 7.2 mg/dl).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 A handful of cases of very mild kidney disease but strong linear GBM staining have been reported. 23,26,29,30 Interestingly, one of these cases was associated with an IgG4-predominant autoantibody specific for a quaternary-structure epitope of the NC1 hexamer of a3, a4, and a5 chains of collagen IV and thus could not be detected using tests based on monomeric Goodpasture antigen. 26 Our patient likely has a circulating monoclonal IgG1k anti-GBM antibody that we have not yet been able to detect.…”
Section: Discussionmentioning
confidence: 99%